Особенности управления преобразователями постоянного тока - Жуйков, В.Я.; Вербицкий, Е.В. (Технічна електродинаміка, 2012)
Features direct current converter are analyzed. Possibility origin of self-excited oscillations are researched. Method of improving output voltage quality parameters are proposed